THE INFLUENCE OF YOUNG COCONUT WATER (COCOS NUCIFERA L.) ON THE DECREASE IN SYSTOLIC BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - mulia mayangsari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2020)
Hypertension is the condition where the blood pressure of systolic more then 120 mmHg and the pressure diastolic more then 80 mmHg (Muttaqin, 2009). Based on the previous study at the Ganding community health center there are many patients got high blood pressure before and after the young coconut water have been given to the sufferer hypertinsion at ganding community heat center, subdistrict ganding, sumenep regency.This research used quasy experiment method, independeny variable of young coconut water and dependent variable blood pressure. The population is from the society at community health center ganding the suffeer hypertension, on March 2017 with sample as many as 18 persons. 9 persons are treatment and 9 persons are control used technique of simple Consicutive sampling. The result of research used paired t test and independent test with α:0,05.In analysis of group control and treatment used independent test got from the value ρ:0,000<α:0,05. It means that H0 rejected so, there is difference blood pressure between the group of treatment and control subdistrict ganding, sumenep regencyThe result of this research expected to be an information and knowledge about one of way in traditional therapy to the sufferer hypertention as efforts in lowering blood pressure. And also developed as reference in the next research. Key words: young coconut, hypertensive